Cryogenic pre-amplifier for liquid xenon applications. (8th September 2021) - Arneodo, F.; Bruno, G.; Conicella, V.; Di Giovanni, A.; Franchi, G.; Manenti, L.
Abstract: Several liquid xenon experiments for rare event searches are using the photomultiplier Hamamatsu R11410 for scintillation light detection. In this work, a low-noise charge pre-amplifier designed for liquid xenon applications is tested at cryogenic temperatures, in combination with this specific photomultiplier. Results will be presented and discussed.